How Time Pressure Matter University Faculties’ Job Stress and Well-Being? The Perspective of the Job Demand Theory - Chen, Zhong; Lee, Tzaichiao; Yue, Xianghua; Wang, Jie (Frontiers in Psychology, 2022)
The work environment of employees has been greatly affected by the COVID-19 pandemic, and many limitations and risks can be seen until now. In addition to employees in firms, the faculty in colleges and universities also suffer from pressure and face challenges. For the purpose of performance assessment and promotion, the faculty not only needs to teach students, but also assumes the time pressure from academic research. This study discusses the process in which the faculty’s subjective well-being is affected, in an effort to learn about the job demands of the faculty under the work environment with a high level of time pressure, and the effect of these time-related job demands on their psychological health. In this study, 347 valid questionnaires were collected from universities in coastal areas of the Chinese mainland. The results show that time-related job demands have a positive impact on time pressure; time pressure has a negative impact on subjective well-being; time-related self-efficacy can significantly mediate the relationship among time-related job demands, time pressure and subjective well-being. On this basis, this study proposes its theoretical and practical implications.